Rural Out-Migration: A Catalyst For Agricultural Development And Environment Regeneration In Bekwarra, Cross River State, Nigeria - Atu, Joy Eko; Abutunghe, Abutunghe Mathew (Advances in Social Sciences Research Journal, 2018)
The rate, frequency and intensity of migration are increasing across the globe with dire consequences to source and receiving areas, however, out-migration can be a catalyst for development and natural resources conservation. Hence, the study examined the impacts of rural out-migration on agricultural development in Bekwarra, Cross River State, Nigeria. Specifically, the study: i. determines the impacts of out migration on agricultural and natural environment ii. the extent to which remittance from out migrants influence agricultural development in Bekwarra, Cross River State. One hypothesis was formulated and tested at 0.05 confidence limit. A survey design was adopted for the study using purposive and simple random sampling technique to elicit responses from three hundred and eighty (380) respondents drawn from the total number of farmers in the area. Findings revealed that out-migration has induced extended fallow time in some instance thereby allowing agricultural land to regain its fertility. Also reduce labour has informed changes from a more diverse cropping system to less intensive non-diverse cropping systems that has implications for the environment and food security of households. Chi-square statistical tool was used to test the stated hypothesis and the findings revealed remittances from migrants have a significant impact on agricultural development. It was recommended among other things that government should provide more social amenities and employment opportunity to curtail the exponential exodus of the youths from the area to other cities.